Different Neural Mechanisms Underlie Non-habitual Honesty and Non-habitual Cheating - Speer, Sebastian P. H.; Smidts, Ale; Boksem, Maarten A. S. (Frontiers in Neuroscience, 2021)
There is a long-standing debate regarding the cognitive nature of (dis)honesty: Is honesty an automatic response or does it require willpower in form of cognitive control in order to override an automatic dishonest response. In a recent study (Speer, Smidts & Boksem, 2020) we proposed a reconciliation of these opposing views by showing that activity in areas associated with cognitive control, particularly the inferior frontal gyrus (IFG), helped dishonest participants to be honest, whereas it enabled cheating for honest participants. These findings suggest that cognitive control is not needed to be honest or dishonest per se but that it depends on an individual’s moral default. However, while our findings provided insights into the role of cognitive control in overriding a moral default, they did not reveal whether overriding honest default behavior (nonhabitual dishonesty) is the same as overriding dishonest default behavior (nonhabitual honesty) at the neural level. This speaks to the question as to whether cognitive control mechanisms are domain-general or may be context specific. To address this, we applied multivariate pattern analysis to compare neural patterns of nonhabitual honesty to nonhabitual dishonesty. We found that these choices are differently encoded in the IFG, suggesting that engaging cognitive control to follow the norm (that cheating is wrong) fundamentally differs from applying control to violate this norm.